Local DNA Repair Inhibition for Sustained Radiosensitization of High-Grade Gliomas - King, Amanda R.; Corso, Christopher D.; Chen, Evan M.; Song, Eric; Bongiorni, Paul; Chen, Zhe; Sundaram, Ranjini K.; Bindra, Ranjit S.; Saltzman, W. Mark (Molecular cancer therapeutics, 2017)
High-grade gliomas, such as glioblastoma (GBM) and diffuse intrinsic pontine glioma (DIPG), are characterized by an aggressive phenotype with nearly universal local disease progression despite multimodal treatment, which typically includes chemotherapy, radiotherapy, and possibly surgery. Radiosensitizers that have improved the effects of radiotherapy for extracranial tumors have been ineffective for the treatment of GBM and DIPG, in part due to poor blood–brain barrier penetration and rapid intracranial clearance of small molecules. Here, we demonstrate that nanoparticles can provide sustained drug release and minimal toxicity. When administered locally, these nanoparticles conferred radiosensitization in vitro and improved survival in rats with intracranial gliomas when delivered concurrently with a 5-day course of fractionated radiotherapy. Compared with previous work using locally delivered radiosensitizers and cranial radiation, our approach, based on the rational selection of agents and a clinically relevant radiation dosing schedule, produces the strongest synergistic effects between chemo- and radiotherapy approaches to the treatment of high-grade gliomas. Mol Cancer Ther; 16(8); 1456–69. ©2017 AACR.